Pengembangan Usaha Pada Mahasiswa setelah Mendapatkan Pendidikan Kewirausahaan - Ani Darliani; Erly Mauvizar; Hayati Hayati; Wirda Wirda (Journal on Education, 2024)
Awareness and the development of entrepreneurial skills among the younger generation or productive age are essential to achieve an improvement in the quality of human resources. Entrepreneurship development is directed towards creating changes in life, based on strengthening the perspective of entrepreneurship education, which can optimize the skills, abilities, and competencies possessed. The research findings indicate that entrepreneurship development by students at STIKes Muhammadiyah Aceh is more focused on earning additional income, assisting parents, and developing their existing skills. Entrepreneurship education has a positive influence by providing knowledge for innovation, becoming more structured, and understanding marketing strategies as well as interactions with customers. To encourage entrepreneurship growth among students, an active role from the university is required in organizing innovative and responsible entrepreneurship education. Universities can provide motivation for students to dare to start or develop their own businesses.